2021
DOI: 10.1007/s00381-021-05126-7
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of cerebello-cortical stimulation for intraoperative neurophysiological monitoring of cerebellar mutism

Abstract: Background Cerebellar mutism can occur in a third of children undergoing cerebellar resections. Recent evidence proposes it may arise from uni- or bilateral damage of cerebellar efferents to the cortex along the cerebello-dento-thalamo-cortical pathway. At present, no neurophysiological procedure is available to monitor this pathway intraoperatively. Here, we specifically aimed at filling this gap. Methods We assessed 10 patients undergoing posterior fossa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…At present, IONM is well established for supratentorial functional areas, brainstem and cerebello-pontine angle, but not for monitoring of the cerebellum itself. Recently, the first study was published on IONM of the cerebello-dentato-thalamo-cortical pathway [ 10 ]. The authors demonstrated that direct stimulation of lobules IV, V, and VI in the anterior cerebellum and lobule VIIB in the posterior cerebellum leads to inhibition of primary motor cortex excitability for transcranial electrical stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…At present, IONM is well established for supratentorial functional areas, brainstem and cerebello-pontine angle, but not for monitoring of the cerebellum itself. Recently, the first study was published on IONM of the cerebello-dentato-thalamo-cortical pathway [ 10 ]. The authors demonstrated that direct stimulation of lobules IV, V, and VI in the anterior cerebellum and lobule VIIB in the posterior cerebellum leads to inhibition of primary motor cortex excitability for transcranial electrical stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…These include, for example: (i) computation of probabilistic connectivity atlas based on segmentation of the cerebellar peduncles, allowing for comparison of WM integrity between patients and controls diffusion maps (207,208); (ii) application of transcranial magnetic stimulation (TMS) technique to provide either negative or positive inhibitory or facilitatory modulation of the primary motor cortex output using an appropriate cerebellar stimulus to deduce injury to the dentato-thalamiccortical circuit and predict postsurgical development of cerebellar mutism (209); (iii) development and validation of reliable procedures for neurophysiological monitoring of the cerebellocortical connectivity. Preliminary results in this field showed the feasibility of reproducing extra-operative conditioning-test paradigm previously adopted for TMS (210).…”
Section: Neurosurgical Implicationsmentioning
confidence: 96%
“…In brain tumor surgery IONM is particularly well-established for preservation of the corticospinal tract ( 13 , 14 ), but asleep mapping and monitoring outside the corticospinal system is lacking. The aim of this opinion paper is to discuss two novel potential IONM techniques allowing to map and monitor functions beyond corticospinal motor function in the anesthetized setting, namely, (A) conditioning of motor output ( 15 , 16 ) and (B) cortico-cortical evoked potentials ( 17 , 18 ). These have been performed under total intravenous anesthesia using Propofol (100–150 μg/kg/min) and Fentanyl (1 μg/kg/min) in continuous infusion, and avoiding muscle relaxants after intubation.…”
Section: Introductionmentioning
confidence: 99%
“…We propose that the CS/TS approach can be successfully performed also by means of direct cortical stimulation in the intraoperative setting, and therefore potentially be used for assessing and potentially monitoring the integrity of specific brain and spine connections, as demonstrated by two recent works from our group, on parietal-motor connectivity ( 15 ) and on cerebello-motor connectivity ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation